Disturbance-observer based control for magnetically suspended wheel with synchronous noise. (March 2018) - Yu, Yuanjin; Yang, Zhaohua; Han, Chao; Liu, Hu
Abstract: A disturbance-observer based method is proposed to attenuate the synchronous vibration of a magnetically suspended wheel (MSW). When the rotary speed is nonzero, the synchronous vibration exists. To analyze this vibration, a precise dynamic of the MSW is researched and the synchronous vibrations model is established. A novel vibration attenuation method is proposed by combining a disturbance observer and a state-feedback method. Using Lyapunov's stability theorem, parameters of the controller are determined. Finally, results of numerical simulations and experiments indicate that the proposed method dramatically reduces the synchronous jitter and thus significantly improves precision of the deflection angle. Highlights: The precise dynamic considering the non-coincidence is analyzed. The model of the synchronous noise is established by modeling the dynamic. A disturbance observer based method is designed to attenuate the synchronous noise. The proposed method is easy to implement and the parameters are easy to obtain. Simulations and experiments base on an engineering production validate the proposed method.